Platelet function in beta-thalassaemia major. Issue 5 (May 1979) - Hussain, M A; Hutton, R A; Pavlidou, O; Hoffbrand, A V
Abstract : Abnormal platelet aggregation was found in eight (44%) of 18 patients with beta-thalassaemia major and transfusional iron overload. The aggregation defect bore no correlation with the degree of hepatic fibrosis, liver function tests, whether or not splenectomy had been performed, the degree of iron overload, haematocrit, platelet count, serum vitamin E level, or leucocyte ascorbate concentration. Only three of the 18 patients showed prolonged bleeding times as well as abnormal platelet aggregation, and only one of these suffered clinically significant haemorrhage. The results show that a proportion of patients with beta-thalassaemia major have abnormal platelet function. It is possible, however, that the in vitro abnormality might be due partly to artefacts induced by manipulations required to remove the abnormal thalassaemic red cells, and this may explain the much lower incidence of significant haemorrhage.